Abundance and Characteristics of Microplastics in Seawater and Corals From Reef Region of Sanya Bay, China - Lei, Xinming; Cheng, Hao; Luo, Yong; Zhang, Yuyang; Jiang, Lei; Sun, Youfang; Zhou, Guowei; Huang, Hui (Frontiers in Marine Science, 2021)
Microplastics (MPs) contamination is widespread in the coral reef ecosystems leading to the exposure of both corals and other biotas. Knowledge gaps still exist concerning patterns in MPs abundance spatially. This work quantified the MPs abundance and characteristics in the seawater and corals in the Sanya Bay, Hainan Island. MPs abundance was detected in the seawater and coral samples ranging from 15.50 to 22.14 items L–1, and 0.01 to 3.60 items polyp–1, respectively. We found the predominant size and type of MPs in seawater and corals were smaller than 2 mm and fiber. Further analysis revealed that the characteristics of MPs in the corals were significantly different from those in the seawater environment, indicating that the MPs are selectively enriched in corals. Furthermore, the MPs particles ingested and retained in coral tissue may be related to the polyp size. This study shows that MPs are present in the whole coral reef region and the coral community structure would be potentially harmed by these contaminants.